Instant Granule Formulation Combining White Sweet Potato Leaves Extract (Ipomoea batatas (L.) Lam.) and Javanese Chili (Piper retrofractum Vahl) - Irawan, Herman; Permata Sari, Indah; Tisnadjaja, Djadjat; Ekawati, Nurlaili; Hertati, Ai; Novianti, Ela; Masaenah, Eem (Sains Natural: Journal of Biology and Chemistry, 2024)
Dengue haemorrhagic fever is a viral infection transmitted by the Aedes aegypti mosquito, which is one of the symptoms is thrombocytopenia. The extract from white sweet potato leaves is recognized for its potential to increase the number of platelet count. This research aimed to develop a formula for an instant granule combining white sweet potato leaves extract with Javanese chili extract meeting taste preferences and societal acceptability. The preparation of the extract was performed by maseration using 70% ethanol and then concentrated with a rotary evaporator. The result was a thick extract which was then dried in an oven at 50℃. The manufacture of instant granule formulations was conducted using wet granulation method. Various formulations were obtained by differentiated concentration of Javanese chili used in the formula (FI 1%, FII 2%, and FIII 3%). The instant granule formulation was evaluated by organoleptic assay and other essential parameters for instant granule, such as moisture content, flow rate, angle of repose, and particle size distribution. The FII 2% formulation emerged as the most acceptable with an average score of 2.17. Non-parametric analysis indicated no significant difference among the three formulas, as the obtained significant value (α) was ≥ 0.05, leading to the acceptance of the null hypothesis H0.